Trade Liberalisation in Europe and the Rest of the World - Cristian Spiridon (CES Working Papers, 2012)
The present paper aims to disseminate how liberalisation processes were conducted around the globe and especially in Europe since the XIXth century up to date. The research objective is to review the liberalisation of trade dynamics and create an image of the architecture of the most important trading blocs. Analysis will be conducted considering the three major regional blocs: Europe, North America and East Asia. The main findings will show that, despite the few mutations that occurred in international trade as a result of the emergence of developing nations as major trade partners, the European Union and the United States remain the economic and trade hegemons.
Keywords: F10; F13; F14; F15; F36; 330; European Union; trade blocs; protectionism; regionalism; trade agreements; multilateral negociations; financial crisis Romania